Qur'an Whiz: Developing an Android-Based Application to Enhance Qur'an Memorization Skills for Elementary School Students - Djainudin, Hamdhan; Saputra, Apry Aditya; Rahmat, Nazaludin Nur; Aprilio, Triandi (Jurnal Prima Edukasia, 2025)
Post-COVID-19, Islamic religious education faced challenges due to mosque restrictions and suspended Qur'anic programs, reducing youth interest in memorization. Technological distractions also prompted shifts in teaching methods to adapt to digital advancements. This study aims to develop the Qur'an Whiz educational game application for Qur'anic memorization using the Takrir method, designed specifically for the Android platform. The research adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as its methodological framework. Iterative testing and validation processes involving material, design, and media experts were conducted to refine the application and ensure its effectiveness and user engagement. The activities carried out at the analysis stage are collecting data through interviews and observations, related to existing problems. Furthermore, implementation is carried out by testing the application in the community, students, material experts, design experts, and media experts. After testing and implementing the product, the final stage is evaluating and perfecting the "Qwizy" application according to suggestions from experts, teachers, students, and the general public. The findings revealed a significant improvement in users' memorization abilities, with the average pretest score of 65 increasing to 85 in the post-test, reflecting a 20-point or 30.77% improvement. The application features a user-friendly interface and interactive elements that enhance user motivation and engagement. This study concludes that "Qur'an Whiz" is an innovative and effective tool for improving Qur'anic memorization, offering an educational and enjoyable learning experience for children in the digital era.